1985
DOI: 10.2337/diacare.8.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Diabetic Retinopathy and Blindness: A Population-based Study in Rochester, Minnesota

Abstract: Among the 1135 Rochester residents discovered to have diabetes in the period 1945-69, the prevalence of retinopathy was 2.6% at the time of initial diagnosis. Among those free of retinopathy at diagnosis of diabetes, the subsequent incidence of any retinopathy was 17.4 per 1000 person-years and for proliferative retinopathy alone was 1.6 per 1000 person-years, based on 12,000 person-years of follow-up. The incidence rate of retinopathy was almost three times greater among residents with insulin-dependent (IDDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 30 publications
(14 reference statements)
6
50
0
Order By: Relevance
“…Nielsen reported a 1-year blind-ness incidence of 3.7% in insulin-treated diabetic patients (1984a). Dwyer and associates estimated a 4-year rate of blindness of 1.6% in all diabetic persons (Dwyer et al 1985). Sjolie & Green found an annual incidence rate of blindness of approximately 1 O/O (Sjdie & Green 1987).…”
Section: Visual Acuitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nielsen reported a 1-year blind-ness incidence of 3.7% in insulin-treated diabetic patients (1984a). Dwyer and associates estimated a 4-year rate of blindness of 1.6% in all diabetic persons (Dwyer et al 1985). Sjolie & Green found an annual incidence rate of blindness of approximately 1 O/O (Sjdie & Green 1987).…”
Section: Visual Acuitymentioning
confidence: 99%
“…One patient developed moderate, visual loss and 2 with moderate visual impairment at baseline improved over the 4-year period. Relatively few prospective population-based studies have been made on the incidence of visual impairment due to diabetes (Nielsen 1984a,b;Dwyer et al 1985;Sjalie & Green 1987;Moss et al 1988;Agardh et al 1993). In the Wisconsin Epidemiology Study, Moss and associates found a 4-years blindness incidence rate of 1.5% in young onset (< 30 years) patients (Moss et al 1988).…”
Section: Visual Acuitymentioning
confidence: 99%
“…etinopathy is the most common complication of type 1 diabetes, affecting 70-100% of all patients (1)(2)(3). The only proven preventive measure is strict glycemic control (4), which alone is not wholly satisfactory because retinopathy still develops in ϳ12% of intensively treated diabetic patients, and the institution of such control places great demands on both patients and health care systems, questioning its true practicality (5).…”
mentioning
confidence: 99%
“…Thus, IDDM is of major importance in health care planning as it affects health primarily through its chronic multisystem complications, rather than by acute metabolic crises related to insulin deficiency [2]. These chronic conditions include diabetic retinopathy [3,4], coronary artery disease [4][5][6], nephropathy [7], neuropathy [8], cerebrovascular disease [8][9][10], and peripheral vascular disease (PVD) [11][12]. Treating IDDM therefore requires a variety of health care resources including hospital physician and general practitioner time.…”
mentioning
confidence: 99%